Aplicação de extratos de algas marinhas em cafeeiro sob deficiência hídrica e estresse salino - Bettini, Marcos de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The effects of two seaweed extract were evaluated in terms of biometric characteristics, water relations, gas exchange and biochemical parameters for two coffee cultivars (Obatã e Catuaí 99). In order to have a better understanding how these products interfere in drought and salt stress tolerance. Two greenhouse trials arranged in randomized blocks with three replications per treatment were conducted with coffee transplants in 5 L pots under drip irrigation. The first drought stress experiment compared three irrigation levels (25%, 50% and 100% of water demand) in both coffee cultivars with two different seaweed extracts treatments and control. This experiment received three drought stress cycles of fifteen days interspersed with two periods of fifteen days of reconditioning. The second salt stress experiment induced with NaCL used same cultivars and seaweed extracts treatments in the first trial. In this case two salt stress cycles of thirty days interspersed with one thirty day period for reconditioning were applied. Seaweed extracts treatments were: A1 - Weekly Applications of diluted Ascophyllum nodosum soluble liquid extract. A2 - One combined application of Ascophyllum nodosum and Lithothamnium calcareum solid extracts. Water deficiency and salt stress treatments presented lower foliar water potential, net photosynthesis, transpiration and leaf area for both cultivars. Seaweed extracts application induced salt and drought stress tolerance. Coffee plants treated with seaweed extracts presented higher leaf area, root weight, stem water potential, carbon assimilation, lower rate Na+/K+, and changes in antioxidant enzymes activities.

O presente estudo relacionou os efeitos da aplicação de dois extratos de algas marinhas às características biométricas, relações hídricas, trocas gasosas e alterações bioquímicas em dois cultivares de café e sua interferência na tolerância à deficiência hídrica (DH) e estresse salino (ES). Foram conduzidos dois experimentos em blocos causalizados, em estufa com mudas de cafeeiro em vasos de 5 L irrigados por gotejamento, com 3 repetições por tratamento. O primeiro experimento sobre DH comparou três níveis de irrigação: D1-25%, D2-50% e D3-100% da necessidade hídrica da cultura em dois cultivares (Obatã e Catuaí 99) e dois tratamentos de extratos de algas e controle, sendo aplicados três ciclos DH, intercalados com dois períodos de recondicionamento. O segundo experimento de ES estudou o efeito da salinidade induzida com NaCl para as mesmas cultivares e para os mesmos tratamentos com extratos de alga. Neste caso foram aplicados dois ciclos de estresse salino intercalados com um período de recondicionamento. Os tratamentos com extratos de alga foram: Alga 1 – Aplicações semanais de soluções do extrato líquido solúvel da alga Ascophyllum nodosum. Alga 2 – Uma aplicação via solo da combinação de extratos sólidos das algas Ascophyllum nodosum e Lithothamnium calcareum. Os tratamentos com DH e ES apresentaram menor potencial hídrico foliar, assimilação de carbono, transpiração e área foliar, independentemente dos cultivares. A aplicação de extratos de alga induziu tolerância a estresses hídrico e salino. Plantas de cafeeiro tratadas com extratos de algas apresentaram maior área foliar, maior massa de raízes, maior potencial de água na folha, menor relação Na+/K+, assimilação de carbono e alterações na atividade de enzimas antioxidativas
Seaweed extracts application in coffee plants under water restrictions and salt stress
Keywords: Stress (Fisiologia); Fotossintese; Alga marinha; Metabolismo; Café - Irrigação; Café - Cultivo; Coffee plantations